The pioneer woman [large type] : black heels to tractor wheels-- a love story - Drummond, Ree (Thorndike Press large print core, 2011)
It was like a romance novel, an old Broadway musical, and a John Wayne western rolled into one. Out for a quick drink with friends, Ree Drummond wasn't looking to meet anyone, let alone a tall, rugged cowboy who lived on a ranch miles away from her cultured, corporate hometown. But before she knew it, she'd been struck with a lightning bolt.